Kite might - Tay, Yinxue (2017)
Kite Might is a comedic 2D digitally animated short designed for kids. It tells the story of a pair of young children from an indigenous tribe who engage in a bet that involves flying a humongous kite or eating one. Drawing inspiration from classic stories such as Aesop’s “Tortoise and the Hare” and the incredibly popular television series “Avatar: The Last Airbender”, our group hopes to tell a simple story imbued with light moral values and at the same time introduce a world that is rich with lore. The following report documents the making of Kite Might, from the early stages of ideation to the final product. It elaborates on the challenges faced by the team as well as the solutions and compromises we had to make in order for this film to be realized.